Helminth fauna parasitizing Pimelodus pohli (Actinopterygii: Pimelodidae) from the upper São Francisco River, Brazil - Sabas,Claudia Silveira São (2014)
The parasite fauna of catfish, Pimelodus pohli, from the São Francisco River Basin is presented. A total of 45 catfish from the upper São Francisco River (45°15′44″W 18°13′25″S), were examined from July 2009 to September 2011. Forty-three catfish (95.5%) were infected by at least one parasite species, with 885 parasite specimens being found, distributed across 17 species: Monogenea (Demidospermus uncusvalidus, Pavanelliella pavanellii, and Scleroductus sp.); Eucestoda (plerocercoids of Proteocephalidea); Digenea (metacercariae of Austrodiplostomum compactum, adults of Auriculostoma platense and Kalipharynx sp., and juvenile of Prosthenhystera obesa); Nematoda (larvae of Contracaecum sp., Hysterothylacium sp., Procamallanus pimelodus, Procamallanus sp., and unidentified of Cucullanidae, and adults of Cucullanus caballeroi, Philometra sp., and Procamallanus freitasi); and Acanthocephala (adults of Neoechinorhynchus pimelodi). Procamallanus freitasi and Scleroductus sp. were the taxa with the highest prevalence. Demidospermus uncusvalidus, P. freitasi, and Scleroductus sp. were the dominant species. The host's sex did not influence parasitic indexes; however, the total length of the catfish did appear to have some influence. The parasites, with except for P. obesa, were registered for the first time in P. pohli, as well as the occurrence of Kalipharynx sp. and C. caballeroi among pimelodid hosts from São Francisco River and South America.